Language Brokering in Healthcare Settings in Spain: An Insight Based on Testimonies - Nevado Llopis, Almudena; Foulquié Rubio, Ana Isabel; Pelea, Alina (English Studies at NBU, 2024)
There were 6,491,502 foreign residents living in Spain in January 2024, a number that indicates a significant increase since the beginning of the 21st century. Among this foreign population, the largest communities are Moroccans, Romanians and British, whose mother tongue is not Spanish. According to the results from several studies conducted over the last decades, when these allophone residents use the Spanish healthcare services, they frequently ask their children to help them communicate with healthcare providers through linguistic and cultural mediation, even when professional interpreting or mediation services are available. How did these children feel while mediating for their parents in this context? Did they have any negative experiences? We intend to provide answers to these questions through semi-structured individual interviews with adults who had mediated for their parents in healthcare settings in Spain when they were children or young adults. These answers contribute to a clear understanding of the consequences of language brokering, thus promoting the use of professional interpreting and mediation services in these settings.